Supporting Teachers in Schools to Improve Their Instructional Practice. Issue 14 (December 2013) - Borko, Hilda; Klingner, Janette
To meet the growing demand for teacher learning opportunities, the educational community must create scalable professional development models and study their effectiveness. In this chapter, we argue that design-based implementation research (DBIR) is ideally suited to these efforts, and we use two research projects in which we are currently involved as illustrative cases: CSR Colorado and Implementing the Problem-Solving Cycle (iPSC). The core of CSR Colorado is Collaborative Strategic Reading, an instructional approach designed to enhance reading comprehension in content classes. The focus of iPSC is the Problem-Solving Cycle, a mathematics professional development (PD) program designed to help teachers improve their instruction through closely examining mathematics problems, student thinking, and pedagogical practices. Each project works with a school district to bring a PD model to scale, and both projects are studying the structures and resources needed to build the district's capacity to sustain the model beyond the duration of the research. The chapter describes each project and discusses the successes and challenges we experienced as we collaborated with the districts and schools to carry them out. By highlighting two very different projects we show how, through different means, it is possible to achieve the same ultimate end of a scaled-up program for improving instructional practices.